2021
DOI: 10.1515/ipp-2020-4022
|View full text |Cite
|
Sign up to set email alerts
|

Basic Study of Extensional Flow Mixing for the Dispersion of Carbon Nanotubes in Polypropylene by Using Capillary Extrusion

Abstract: This study evaluated the mixing effect of simple uniaxial extensional flow for the dispersion of multiwalled carbon nanotubes (MWCNTs) into polypropylene (PP) as a nonpolar matrix. An only converging flow allowed for a high strain rate and was suitable for the compounding process. The extensional flow was characterized from the entrance pressure drop (ΔP0) at the converging section. Thus, in this study, capillary extrusion was employed to generate uniaxial extensional flow. Based on the hypothesis that the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a previous study, we showed that the simple uniaxial extensional flow generated by an orifice die in a capillary rheometer called “converging flow” could enhance the dispersion state of carbon nanotubes (CNTs) in a polypropylene matrix with a higher entrance pressure drop related to extensional stress. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that the simple uniaxial extensional flow generated by an orifice die in a capillary rheometer called “converging flow” could enhance the dispersion state of carbon nanotubes (CNTs) in a polypropylene matrix with a higher entrance pressure drop related to extensional stress. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that the simple uniaxial extensional flow generated by an orifice die in a capillary rheometer called "converging flow" could enhance the dispersion state of carbon nanotubes (CNTs) in a polypropylene matrix with a higher entrance pressure drop related to extensional stress. [4] In the TSE, kneading blocks (KB), which are a type of screw segment, produce an intensive shear flow field, and dispersive mixing and distributive mixing are controlled by an offset angle, a number of discs, and a specific disc width. [5] However, due to the limitation of the mixing capacity of KB for the dispersion of nanofillers, many researchers have attempted to increase the extensional flow components using convergence-divergence (C-D) geometry in the mixing segments and devices.…”
Section: Introductionmentioning
confidence: 99%